In-situ expression of Interleukin-18 and associated mediators in the human brain of sALS patients: Hypothesis for a role for immune-inflammatory mechanisms. (January 2016) - Kadhim, Hazim; Deltenre, Paul; Martin, Jean-Jacques; Sébire, Guillaume
Abstract: Recent studies reported over-expression of a cytokine (Interleukin (IL)-18) in the serum of sporadic amyotrophic lateral sclerosis (sALS) patients. Here, we report on the first-time detection of in-situ expression of activated IL-18 in the human brain in sALS patients. We also detected cerebral in-situ expression of key-molecules known to be closely related to the molecular network associated with the activation/secretion of IL-18 cytokine, namely, the receptor-interacting serine/threonine-protein kinase 3 (RIPK3 or RIP3), NOD-like receptor pyrin domain containing 3 (NLRP3)-inflammasome, and activated caspase-1. These findings suggest and allow to hypothesize that there might be a role for this cytokine network in molecular mechanisms associated with or implicated in the physiopathology of this neurodegenerative disorder.